2008
DOI: 10.1021/ja800763j
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of C5′ Radicals of Purine Nucleosides under Oxidative Conditions

Abstract: The factors that influence the reactivity of C5' radicals in purine moieties under aerobic conditions are unknown not only in DNA, but also in simple nucleosides. 5',8-Cyclopurine lesions are the result of a rapid C5' radical attack to the purine moieties before the reaction with oxygen. These well-known lesions among the DNA modifications were suppressed by the presence of molecular oxygen in solution. Here we elucidate the chemistry of three purine-substituted C5' radicals (i.e., 2'-deoxyadenosin-5'-yl, 2'-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 60 publications
3
68
0
Order By: Relevance
“…6 In this work we considered for comparison the 8-substituted guanosines. The spectral changes obtained from the pulse irradiation of a N 2 O-saturated unbuffered aqueous solutions of 1 mM 8-(2-hydroxypropan-2-yl)guanosine (7) or 8-bromoguanosine (8) are shown in Figures 1 and 2. The behavior in both cases was very similar to the analogous reaction of guanosine.…”
Section: Chemical Research In Toxicologymentioning
confidence: 99%
See 1 more Smart Citation
“…6 In this work we considered for comparison the 8-substituted guanosines. The spectral changes obtained from the pulse irradiation of a N 2 O-saturated unbuffered aqueous solutions of 1 mM 8-(2-hydroxypropan-2-yl)guanosine (7) or 8-bromoguanosine (8) are shown in Figures 1 and 2. The behavior in both cases was very similar to the analogous reaction of guanosine.…”
Section: Chemical Research In Toxicologymentioning
confidence: 99%
“…The consumption of 1b was accompanied by the formation of two main products, identified as guanine and the hydrated 5 0 -aldehyde 5. 8 The majority of cyclonucleosides (4) were replaced by hydrated 5 0 -aldehyde 5 (∼8%), which suggests that the oxygen concentration would be high enough to trap most of the C5 0 radicals prior to cyclization, whereas guanine (free base) is formed via well-known pathways of C1 0 , C3 0 and C4 0 sugar radicals trapped by oxygen. 9 The above considerations at the nucleoside level are strictly connected to DNA lesions.…”
Section: ' Introductionmentioning
confidence: 99%
“…10% by hydrogen abstraction from C5′ position. 7 Our chemical biology approach for the libraries of purine 5',8-cyclo-2'-deoxyribonucleosides (including labeled compounds) is illustrated in Figure 7, with the identification of these lesions in oligonucleotides as well as in DNA samples obtained from various sources such as, for example, treated under ionizing radiation conditions, as mimic of radical stress conditions.…”
Section: Gamma Radiolysis Of Dna Aqueous Solutionsmentioning
confidence: 99%
“…We focused our interest on the smallest tandem lesions, which are purine Bio-inspired synthetic procedures of compounds 1-4 were developed starting from 8-bromopurine derivatives under or photolysis. 7,12 These procedures involve a radical cascade reaction that mimics the DNA damage mechanism of formation of 5',8-cdAdo and 5',8-cdGuo lesions. From biological perspectives, it was found that these lesions accumulate with aging in a tissue-specific manner (liver>kidney>brain), providing evidence that DNA repair mechanisms are inadequate to preserve the genetic material from these lesions.…”
Section: Gamma Radiolysis Of Dna Aqueous Solutionsmentioning
confidence: 99%
“…0 ,8-cyclopurine-2 0 -deoxynucleosides [1][2][3][4][5]. Radicals centered at each of the C1 0 , C2 0 , C3 0 , C4 0 , and C5 0 carbon atoms of the 2 0 -deoxyribose moiety of DNA have been observed experimentally [6][7][8] (see Fig.…”
mentioning
confidence: 99%